NANAY language stimulation aid for infants and toddlers in orphanages in the Philippines - Maglasang, Angelie C.
Stimulation of the senses in children during early years of life is vital for their brain development that the lack of it will inhibit physical, mental and social problems n children as they grow. These problems will hinder them from becoming a functional citizen in their own community. Through explorative play and human interactions, stimulation are required. However, in orphanages, these stimulation are limited. The environment of orphanages compared to actual households offer limited space for exploration and movement. Moreover, due to a big difference a child-caregiver ratio, it is barely possible for a single caregiver to obtain one-on-one interaction with a single child vital for speech development. As this problem persist, social interaction with peers and other life skills will be difficult for these children to acquire, hence will hold back the children in becoming into their full well-being. With this, an alternative interaction to stimulate audition for speech acquisition designed to be used during play is conceptualized. NANAY, a language stimulation aid for infants and toddlers in orphanages in the Philippines will be of assistance to caregivers in providing stimulation for sensory motor skills that are possibly at risk under orphanage care.